DAMPAK BULLYING TERHADAP HARGA DIRI INDIVIDU PADA MASA DEWASA MUDA - Nadiyah Ameylia; Melyani Sutra Dewi; Callista Alodya J; Sinta Purnamasari; Ahmad Najib; Abdul Rahim; Anggi Agusti; Ratu Tazkiyatun Nufus; Yesi Anggun Sari (Journal of Communication and Social Sciences, 2023)
Victim of bullying are always associated with many problem, especially in terms of mental health, one of which is adolescent self-esteem. This research is motivated by the rise of bullying cases that occur among adolescent. Where bullying is an action taken by individuals or groups against other individuals who are considered weak. Bullying can take the form of physical aims to determine the forms of bullying. The causes of bullying, and the impect of bullying. The research subject are students. The data collection technique used was a correlational quantitative method using a sample of 98 students by filling out a questionaire to the perpetratorsvand vicktims of bullying. The method used in this study is Spearment analysis with the help of IBM SPSS application and, based on the result of processing the data, it was found that there was no significant correlation between bullying behavior and self esteem in adolescent among student at Raden Fatah State Islamic University Palembang. The results of the analysis show that the value of the correlation coeficient between the two variables is very low (0.063) and does nor reach the specifiend significance level (ρ < 0,05).